127k views
2 votes
Find f(-2).

F(x)=9x^2-5x+2

A. 14

B. 18

C. 28

D. 48

1 Answer

7 votes

Answer:

D

Explanation:

First, we must substitute the x's in the equation for -2

So the equation will look like

f(-2)= 9
(-2)^(2) - 5(-2) +2

Now we can simplify the equation by solving the exponents


-2^(2)= 4

Now we enter that back into our previous equation which will now look like

f(-2)=9(4)-5(-2)+2

Next, multiply all the parenthesis

9(4)= 36

And

-5(-2)=10

Again, we must enter those values back into our equation so it will now look like

f(-2)=36+10+2

Now we just add the numbers to solve

So the answer is 48

User MattyG
by
7.0k points